Method for producing magnesium modified activated carbon using microwaves, magnesium modified activated carbon produced thereby, and phosphate removal method using the same

Microwave treatment of magnesium-impregnated activated carbon addresses the energy inefficiency of high-temperature calcination, providing a cost-effective and efficient method for phosphate removal from water systems.

KR103042215B1Active Publication Date: 2026-11-03KNU IND COOPERATION FOUND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020230185463
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-11-03
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

Existing methods for manufacturing magnesium-modified activated carbon are energy-intensive due to high-temperature calcination, and there is a need for high-performance, low-cost adsorbents to effectively remove low-concentration phosphates from water systems.

Method used

A method involving impregnating activated carbon with magnesium and treating it using microwaves under specific conditions (300~500 W, 150~250℃, 250~350 psi, and up to 20 minutes) to produce magnesium-modified activated carbon, which is then used to remove phosphates by adjusting wastewater pH to 2 to 10.

Benefits of technology

The method reduces energy consumption and enhances phosphate removal efficiency, with improved adsorption characteristics and reduced processing time, making it more efficient and cost-effective for low-concentration phosphate removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112023142300313-PAT00013_ABST
    Figure 112023142300313-PAT00013_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing magnesium-modified activated carbon using microwaves, magnesium-modified activated carbon manufactured thereby, and a method for removing phosphate using the same. The present invention provides a method for manufacturing magnesium-modified activated carbon comprising: (1) a step of preparing activated carbon; (2) a step of impregnating the activated carbon with magnesium; and (3) a step of treating the magnesium-impregnated activated carbon in a microwave oven.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing magnesium-modified activated carbon using microwaves, magnesium-modified activated carbon manufactured thereby, and a method for removing phosphate using the same. Background Technology

[0002] Phosphorus is an essential element for the normal functioning of all living organisms. However, excessive increases in phosphate concentrations in water systems promote the growth of algal blooms and reduce dissolved oxygen. This not only adversely affects aquatic life but also disrupts the food chain and leads to water quality deterioration. Phosphates are considered major pollutants because they can accumulate in water systems and reach high concentrations due to industrial and agricultural activities and sewage discharges. Phosphate-related problems have caused environmental and economic damage globally for decades and are a matter of worldwide concern. Many countries are tightening discharge standards to mitigate the damage caused by phosphate emissions and require effective treatment methods. To date, chemical precipitation, biological treatment, and physical adsorption have been primarily applied to remove phosphates from water and wastewater. However, chemical precipitation requires the extensive use of metal salt coagulants to achieve low phosphate concentrations, resulting in excessive sludge and high operating costs. While biological advanced water treatment methods are effective in reducing phosphate levels to 1 mg P / L, they require long-term microbial adaptation and exhibit low removal efficiency at low phosphate concentrations. Adsorption is a technology in which substances are adsorbed onto the surface of an adsorbent through covalent bonding and electrostatic interactions. It is considered a promising technology due to its advantages, such as low cost, rapid and efficient removal, reusability, and reduced sludge generation. In particular, adsorption is known to be an effective method when phosphate concentrations are low. Therefore, research on high-performance and low-cost adsorbents for low-concentration phosphate is necessary. Adsorbents are one of the key components of the adsorption process. Accordingly, various types of adsorbents for phosphate removal, such as activated carbon, zeolite, and hollow silica, are being studied. Among these, activated carbon is widely used due to its broad range of pollutant adsorption characteristics and large specific surface area.However, activated carbon generally exhibits low adsorption characteristics for anionic adsorbates. The surface of activated carbon has a negative charge due to a large number of carboxyl and phenolic groups, which limits the actual adsorption capacity of phosphates.

[0003] Various studies are being conducted to modify activated carbon using metals that have a high affinity for phosphates. For example, research is underway regarding the phosphate removal and adsorption characteristics using metals such as Fe, La, and Zr. Among metals, Magnesium (Mg) is an alkaline earth metal present in the Earth's crust at a concentration of 2%; due to its small ionic radius, it has a high charge density and is attracting attention as a metal with high affinity for phosphates. Currently, active attempts are being made to modify carbon-based adsorbents, such as activated carbon and biochar, by impregnating them with Mg. However, a problem exists in the manufacturing process of Mg-modified adsorbents, as the high-temperature calcination step requires a significant amount of energy and time. In contrast, microwave irradiation ensures a uniform energy distribution throughout the material, enabling efficient internal heat transfer. Because microwave irradiation requires a relatively short processing time and consumes less energy, it is an environmentally friendly and simple alternative to high-temperature calcination.

[0004] This invention aims to evaluate the removal efficiency of low-concentration phosphates using Mg-modified activated carbon. It presents modification conditions, such as the optimal impregnation time, Mg impregnation solution concentration, and microwave irradiation time, for Mg modification on the surface of activated carbon using microwaves. Since pH and reaction time act as critical factors in removing phosphates from wastewater, optimal values ​​are presented to enhance the phosphate removal rate. To facilitate the application of the manufactured adsorbent to process design and operating conditions, the results are evaluated by applying isothermal adsorption experiments and reaction rate models. Additionally, the power consumption (kWh / g) and treatment time per unit mass of adsorbent during microwave irradiation are presented. Prior art literature

[0005] Korean Registered Patent Publication No. 10-2069492 The problem to be solved

[0006] The present invention aims to provide a method for manufacturing magnesium modified activated carbon having an improved phosphate removal rate, magnesium modified activated carbon manufactured thereby, and a method for removing phosphate using the same.

[0007] The purposes of the present disclosure are not limited to those mentioned above, and other purposes and advantages of the present disclosure not mentioned may be understood from the following description and will be more clearly understood from the embodiments of the present disclosure. Furthermore, it will be readily apparent that the purposes and advantages of the present disclosure can be realized by the means and combinations thereof set forth in the claims. means of solving the problem

[0008] The present invention provides a method for manufacturing magnesium-modified activated carbon, comprising: (1) a step of preparing activated carbon; (2) a step of impregnating the activated carbon with magnesium; and (3) a step of treating the magnesium-impregnated activated carbon in a microwave oven.

[0009] The above step (3) is performed under conditions of 300~500 W, temperature 150~250℃, maximum pressure 250~350 psi, and 0 minutes or less than or equal to 20 minutes.

[0010] The activated carbon in step (1) above is granular activated carbon of 0.1 to 1.0 mm.

[0011] Step (2) above is a step performed by mixing activated carbon into an aqueous solution of 0.5-3 M Mg.

[0012] The above (2) step is a step performed by mixing activated carbon into a 1 M Mg aqueous solution.

[0013] The above (2) step is a step performed for a period of time greater than 1 hour and less than or equal to 6 hours.

[0014] The present invention also provides magnesium modified activated carbon produced by the above manufacturing method.

[0015] The present invention also provides a method for removing phosphate, comprising the steps of: preparing wastewater containing phosphate; adjusting the pH of the wastewater to a range of 2 to 10; and removing phosphate from the wastewater using magnesium-modified activated carbon.

[0016] The above phosphate is H3PO4 and H2PO4 in wastewater - , HPO4 2- , PO4 3- It exists in the form of Effects of the invention

[0017] The present invention can provide a method for manufacturing magnesium modified activated carbon having an improved phosphate removal rate, magnesium modified activated carbon manufactured thereby, and a method for removing phosphate using the same.

[0018] According to the present invention, a modification method with reduced power consumption in activated carbon modification can be provided. Brief explanation of the drawing

[0019] Figure 1 shows a flowchart of the method for manufacturing magnesium-modified activated carbon using microwaves according to the present invention. Figure 2 shows the phosphate removal efficiency using the magnesium modified activated carbon of the present invention according to concentration, impregnation time, and microwave irradiation time. Figure 3 shows the phosphate removal efficiency using the magnesium modified activated carbon of the present invention according to pH and reaction time. Figure 4 shows a pseudo-first-order reaction rate model and a pseudo-second-order reaction rate model of the magnesium-modified activated carbon and unmodified activated carbon of the present invention. Figure 5 shows the Langmuir and Freundlich isotherm adsorption models of the magnesium-modified activated carbon and unmodified activated carbon of the present invention. Figure 6 shows SEM images of granular activated carbon before modification, granular activated carbon after magnesium solution impregnation, and magnesium-modified activated carbon after microwave irradiation. Specific details for implementing the invention

[0020] According to one embodiment of the present invention, a method for manufacturing magnesium-modified activated carbon is provided, comprising: (1) a step of preparing activated carbon; (2) a step of impregnating the activated carbon with magnesium; and (3) a step of treating the magnesium-impregnated activated carbon in a microwave oven.

[0021] The above step (3) is performed under conditions of 300~500 W, temperature 150~250℃, maximum pressure 250~350 psi, and 0 minutes or less than or equal to 20 minutes. Preferably, it is performed in an air atmosphere under conditions of irradiation intensity 400 W, temperature 200℃, maximum pressure 300 psi, and irradiation time 10 minutes.

[0022] The activated carbon in step (1) above is granular activated carbon with a diameter of 0.1 to 1.0 mm. Preferably, it is granular activated carbon with a diameter of 0.425 to 0.85 mm.

[0023] Step (2) above is a step performed by mixing activated carbon into a 0.5-3 M Mg aqueous solution. Preferably, it is a step performed by mixing activated carbon into a 1 M Mg aqueous solution.

[0024] The above (2) step is a step performed for a period of time greater than 1 hour and less than or equal to 12 hours. Preferably, it is performed for 2 hours.

[0025] The present invention also provides magnesium modified activated carbon produced by the above manufacturing method.

[0026] The present invention also provides a method for removing phosphate, comprising the steps of: preparing wastewater containing phosphate; adjusting the pH of the wastewater to a range of 2 to 10; and removing phosphate from the wastewater using magnesium-modified activated carbon. The pH range is preferably 2 to 4.

[0027] The above phosphate is H3PO4 and H2PO4 in wastewater- , HPO4 2- , PO4 3- It exists in the form of

[0029] The present invention will be explained in more detail below through examples and experimental examples. However, these examples and test examples are intended to illustrate the present invention, and the scope of the present invention is not limited to these examples and test examples.

[0030] Experimental method

[0031] Experimental materials

[0032] In this experiment, KH2PO4 (Daejeong Hwakum, South Korea) was used as the adsorbent for the production of synthetic wastewater, and granular activated carbon (GAC) for water treatment (Samchully Carbotec, South Korea) was used as the adsorbent. The GAC was ground and sieved through standard 20 and 40 mesh sieves to separate GAC particles of 0.425–0.85 mm. The GAC was washed three times with distilled water, dried in a 105°C drying oven for 24 hours, and then stored in a desiccator (VUVOH-520SA, AS ONE, Japan). MgCl2⁶H2O (Daejeong Hwakum, South Korea) was used to prepare a 0.5–3 M Mg impregnation solution. 10 g of GAC was placed in an Erlenmeyer flask containing 150 mL of the Mg impregnation solution and mixed for 3 hours using a shaking incubator (VS-8480, Vision Science, South Korea). Subsequently, the activated carbon was separated, washed three times with distilled water and once with anhydrous ethyl alcohol (99.5%, Daejeong Hwakum, South Korea), dried in a drying oven for 3 hours, and then cooled to room temperature in a desiccator. 1 g of the dried Mg-impregnated activated carbon was placed in a Teflon cell with 20 mL of distilled water and treated in an air atmosphere using a microwave accelerated reaction system 5 (CEM Corporation, USA) under conditions of irradiation intensity 400 W, set temperature 200℃, maximum pressure 300 psi, and irradiation time 0-20 minutes (Fig. 1). The treated adsorbent was washed with distilled water and dried, and the completed magnesium-modified activated carbon was named Mg-GAC.

[0034] Adsorption experiment method

[0035] Synthetic wastewater with a concentration of 2 mg P / L was prepared by adding KH2PO4 to distilled water, and the pH was adjusted using HCl (35-37 wt%, Daejeong Chemical) and NaOH (99%, Daejeong Chemical) 0.1-1 N. 50 mL of synthetic wastewater and 3 g / L of adsorbent were injected into a 100 mL Erlenmeyer flask, and the reaction was carried out in a shaking incubator at a temperature of 25°C and a stirring speed of 180 rpm. After the reaction, the adsorbent was separated using a glass fiber filter (GF / C), and the absorbance was measured using a UV-VIS spectrophotometer (Libra S60, Biochrom, UK). The results were quantified as phosphate concentration using the Ascorbic Acid Method of the Standard Method. The adsorption capacity and removal efficiency can be calculated using Equations 1 and 2 below.

[0036]

[0037] At this time, C i is the initial phosphate concentration (mg / L), C e ε is the phosphate effluent concentration (mg / L), m is the amount of dry adsorbent injected (g / L), and q e is the adsorption capacity (mg / g), E p represents the phosphate removal efficiency (%). After deriving optimal modification conditions such as impregnation concentration, time, and microwave irradiation time, experiments were conducted in the order of presenting the optimal pH, reaction time, and isothermal adsorption equation for phosphate removal, and the optimal conditions for each experiment were used as parameters for subsequent experiments.

[0038] pH

[0039] pH is one of the most important factors determining the removal rate in adsorption reactions. Depending on the change in pH, phosphate is converted into H3PO4 and H2PO4 - , HPO4 2- , PO4 3- It appears in the form of etc. pH of point zero charge (pH) which determines the surface charge depending on the type of adsorbentpzc A difference occurs and pH is pH pzc When the pH is lower, the surface charge becomes positive, which is favorable for the chemical adsorption of anionic substances. In this experiment, to evaluate the effect of initial pH on adsorption, experiments were conducted on GAC and Mg GAC at different pH levels by adjusting the pH from 2 to 10.

[0040] reaction rate

[0041] Various kinetic models have been proposed to analyze reaction rates, which play a crucial role in process design and modeling control. Through kinetic analysis, the behavior of adsorbents and adsorption control mechanisms can be studied, and the reaction rates between the adsorbent and the adsorbate can be determined. To evaluate the phosphate adsorption reaction rates of Mg-GAC and GAC, phosphate removal efficiency was measured by varying reaction times from 15 to 240 minutes. Samples at the end of each reaction time were separated from the adsorbent, sealed, and stored. After all experiments were concluded, phosphate concentrations were measured simultaneously, and the reaction rates were evaluated by applying the results to kinetic models.

[0042] Isothermal adsorption experiment

[0043] Isothermal adsorption experiments compare the relationship between the maximum adsorption capacity and changes in the initial concentration of the adsorbate and the amount of adsorbent injected when adsorption equilibrium is reached at a constant temperature. By controlling the amount of adsorbent injected according to the initial concentration, the effluent concentration can be managed, thereby achieving an effective and economical adsorption process. In this experiment, the maximum adsorption capacity of Mg-GAC and GAC was investigated in the low concentration range of 0.5-10 mg P / L, and the performance of the adsorbents was compared by comparing the factors of the isothermal adsorption equation generated by substituting them into an isothermal adsorption model.

[0044] Adsorbent properties

[0045] Field emission scanning electron microscope (FE-SEM, Hitachi S-4800, Japan) and energy dispersive X-ray spectrometer (EDS, Hitachi S-4800, Japan) were used to analyze the chemical composition of the adsorbent surface and surface changes prior to modification. Nitrogen gas was adsorbed onto the adsorbent surface at 77.3 K using a specific surface area analyzer (6890GC, Quantachrome, Austria), and the amount of adsorbed nitrogen gas was measured. The specific surface area (S) was then calculated using the formula developed by Brunauer, Emmett, and Teller. BET ) calculated.

[0047] result

[0048] Modification conditions

[0049] Phosphate removal efficiency varied according to impregnation solution concentration; it was highest in the 1 M M impregnation solution (87.5%), followed by 53.6% at 0.5 M, 59.7% at 2 M, and 25.8% at 3 M (Fig. 2(a)). Above 1 M, phosphate removal efficiency decreased as the concentration increased, which is presumed to be due to Mg adsorbing to the adsorbent in the form of large crystals, thereby clogging the micropores. Phosphate removal efficiency was low at 59.6% after 1 hour of impregnation but increased to 85.2% after 2 hours, and did not change significantly beyond 2 hours (Fig. 2(b)). In Mg-GAC without microwave irradiation, the phosphate removal efficiency was 56.0%, which was lower than that of GAC (63%), but showed a tendency to increase as the microwave irradiation time increased (Fig. 2(c)). The set temperature of 200℃ was reached at an irradiation time of 8 minutes, and performance did not increase significantly within 6% at 10 minutes or more (83.8-89.6%), and the maximum removal efficiency (89.6%) was observed at an irradiation time of 14 minutes.

[0050] pH

[0051] Phosphate removal efficiency was highest at pH 4 for both Mg-GAC and GAC, and decreased as pH decreased or increased relative to pH 4 (Fig. 3(a)). When pH increased from 4 to 10, phosphate removal efficiency decreased from 90.0% to 33.9% for Mg-GAC and from 62.1% to 29.0% for GAC. As pH decreased, pH pzc As the difference increases, the surface becomes positively charged and OH- - It is presumed that the removal rate increases because the ion concentration decreases. The difference in removal efficiency between Mg-GAC and GAC according to pH was found to be 5.5–10.0% at pH 2–3, 27.9–29.5% at pH 4–6, and 4.9–11.7% at pH 7–10. At pH 4–6, phosphate species H2PO4 - It appears that the difference is greatest because the adsorption reaction proceeds more actively due to its lower chemical bond energy compared to other species. At pH 2–3, removal efficiency decreased sharply regardless of the type of adsorbent. This is because H2PO4, which is favorable for adsorption at low pH values ​​below 3, - This is because it is reduced to H3PO4, which exhibits electrical neutrality, weakening the electrostatic attraction with the adsorbent and reducing the adsorption reaction.

[0052] reaction rate

[0053] Phosphate removal efficiency was 57.1% for Mg-GAC and 40.1% for GAC at a reaction time of 15 minutes, and 91.9% for Mg-GAC and 63.6% for GAC at 240 minutes, indicating that Mg-GAC was superior at all reaction times (Fig. 3(b)). The efficiency difference between the adsorbents was 17.0% at 15 minutes and 28.3% at 240 minutes, showing an increase as the reaction time lengthened. Although the reaction time increased by one hour from 180 minutes to 240 minutes, the difference in removal efficiency was 0.5% for Mg-GAC and 0.7% for GAC; since the increase was not significant within 1%, the maximum adsorption capacity (q) at 180 minutes... max It was assumed that it reaches ). At this time, q max ε₀ is 0.609 mg / g for Mg-GAC and 0.419 mg / g for GAC. To analyze the reaction rates of Mg-GAC and GAC, a pseudo-first-order reaction rate model and a pseudo-second-order reaction rate model were applied to commonly used equations and compared. The pseudo-first-order reaction rate model Equation 3 can be expressed as the linear Equation 4.

[0054]

[0055] Here, k1 is the pseudo-first-order rate constant (min -1 ), qt is the phosphate adsorption amount per adsorbent injection amount at reaction time t (mg / g), q e ε represents the phosphate adsorption amount per amount of adsorbent injected at equilibrium (mg / g), and t represents the reaction time (min). k1 is Mg-GAC 0.021 min -1 , GAC 0.028 min -1 It appeared as. q e is Mg-GAC 0.071 mg / g, GAC 0.052 mg / g, and R 2 The values ​​were found to be 0.978 for Mg-GAC and 0.968 for GAC (Fig. 4(a)). The pseudo-second-order reaction rate model Equation 5 can be represented as the linear Equation 6.

[0056]

[0057] Here, k2 represents the pseudo-second-order rate constant (g / mg·min). k2 is 0.120 g / mg·min for Mg-GAC and 0.130 g / mg·min for GAC, and q e It was found to be Mg-GAC 0.640 mg / g and GAC 0.471 mg / g. At this time, R 2 ε₀ is 0.997 for Mg-GAC and 0.994 for GAC (Fig. 4(b)). For both adsorbents, R₀ in the pseudo-secondary equation 2 The value was higher than that of the pseudo-first equation, which means that the pseudo-secondary model is more suitable for phosphate adsorption. In the pseudo-first equation, q e wa q max The difference is GAC 0.36 mg / g and Mg-GAC 0.54 mg / g, whereas the pseudo-secondary formula is GAC 0.03 mg / g and Mg-GAC 0.05 mg / g, R 2 Similarly, it can be seen that a pseudo-secondary model is more suitable. The decrease in adsorbate concentration over time is similar to previous studies showing that a pseudo-secondary model is more suitable in batch reactions accompanied by a decrease in adsorption rate. Most previous studies also showed that a pseudo-secondary model is suitable in phosphate adsorption experiments on metal-modified activated carbon.

[0058] Isothermal adsorption experiment

[0059] The factors derived by applying them to the commonly used Langmuir and Freundlich isotherm adsorption models were compared. The Langmuir isotherm was first studied to represent the amount of gas adsorbed by an adsorbent and assumes that no interactions occur between adsorbate molecules and that monolayer adsorption takes place uniformly at the adsorption sites. Equation 7 is the Langmuir isotherm and can be expressed as the linear form of Equation 8.

[0060]

[0061] Here, q mLangmuir monolayer maximum adsorption capacity (mg P / g), K L ε is the Langmuir constant, representing the affinity between the adsorbent and the adsorbate. q m Mg-GAC is 1.37 mg / g, GAC is 1.12 mg / g, and K L The values ​​were found to be Mg-GAC 5.87 and GAC 0.61. At this time, R2 was Mg-GAC 0.995 and GAC 0.948 (Table 1, Fig. 5(a)).

[0062]

[0063] Mg-GAC is q compared to GAC m 1.22 times, K L It was found to be 9.60 times higher. The results showed that adsorption capacity increased with increasing concentration, and C e Since the two linear equations do not intersect at > 0 and the slope of the isothermal adsorption equation for Mg-GAC is smaller than that of GAC, it means that Mg-GAC has superior adsorption performance compared to GAC at all concentrations (Fig. 5(a)). R, another indicator for judging adsorption suitability. L is a dimensionless constant and can be expressed by Equation 9.

[0064]

[0065] R L = 0 is K L Since this occurs when is very large, it implies irreversible adsorption with strong adsorption intensity. 0 < R L For < 1, K L and C i Since is positive, it is found in normal adsorption reactions. In this case, K L and R L R is in an inverse relationship L This means that an adsorbent with a lower R is a more suitable adsorbent. L = 1 is K L It occurs at = 0, meaning that all adsorption processes have concentration as the sole factor, and this is called linear adsorption. R L In 1, K LThis is negative and occurs during the desorption reaction, meaning it is unsuitable for use as an adsorbent. R L C i With Mg-GAC at 0.02-0.25 and GAC at 0.14-0.77 at 0.5-10 mg P / L, it can be seen that both adsorbents are suitable for use, but Mg-GAC is more effective.

[0066] The Freundlich isotherm equation is similar to Langmuir's assumption, but it assumes differently that multilayer adsorption occurs and the differential heat of adsorption decreases exponentially as adsorption proceeds on the surface. Equation 10 is the Freundlich isotherm equation, and by taking the logarithm of both sides, it can be expressed as the linear Equation 11.

[0067]

[0068]

[0069] Here, n is the Freundlich sensitivity constant, where a value greater than 2 indicates a fit for low-concentration adsorption, and K F represents the Freundlich capacity factor. n is 4.03 for Mg-GAC and 2.07 for GAC, and K F It was found to be 0.91 for Mg-GAC and 0.36 for 279 GAC. In this case, R2 is 0.995 for Mg-GAC and 0.996 for GAC (Table 1, Fig. 5(b)). For Mg-GAC, n is 1.95 times higher than GAC, and K F ...was found to be 2.58 times higher. Since the R2 values ​​of the Freundlich and Langmuir equations were identical, it can be concluded that both models fit Mg-GAC under the conditions of this experiment. Furthermore, as the phosphate concentration increased, q e Although it increases, the phosphate removal efficiency was 91.7% at 2 mg / L, 98.3% at 1 mg P / L, and 99.9% at 0.5 mg P / L. This indicates that the adsorption method is effective at low phosphate concentrations.

[0070] Characteristics of Mg-GAC

[0071] SEM confirmed that both GAC and Mg-GAC before and after microwave irradiation had a heterogeneous porous structure (Fig. 6). More particles were observed on the surface of Mg-GAC before microwave irradiation (Fig. 6(b)) compared to the surface of GAC (Fig. 6(a)), which are presumed to be in the form of Mg crystals. On the surface of Mg-GAC after microwave irradiation (Fig. 6(c)), cubic particles appeared in a clustered form, which is presumed to be due to MgCl2 being converted into MgO crystals under high-temperature conditions caused by microwaves (Equations 12, 13).

[0072]

[0073]

[0074] As a result of analyzing the chemical composition (C, O, Mg, N, P) of the adsorbent surface using EDS, C and O were the major elements, and the Mg composition ratio was observed to vary across various regions of the adsorbent. In the region showing the highest Mg composition ratio, the Mg composition ratio increased 40-fold after impregnation (Table 2).

[0075]

[0076] This demonstrates that Mg was successfully impregnated onto the surface of activated carbon through impregnation, and the Mg content in this study using microwaves was found to be approximately 1.5 times higher compared to previous studies that modified the activated carbon surface with Mg through high-temperature calcination. SBET is Mg-GAC 1,036 m 2 / g, GAC 1,048 m 2 After modification to / g, it decreased by approximately 1.1%. Activated carbon modified with Fe using high-temperature calcination S BET Although it decreased by 35.7%, microwave-modified Mg-GAC did not have Mg particles blocking the micropores, so S BET It is estimated that it has not decreased significantly. S BETAlthough a decrease in entails a decrease in adsorption rate and capacity, this microwave modification method S BET While maintaining it, the adsorption rate and capacity were increased using magnesium.

[0077] Power consumption

[0078] The power consumption per unit of adsorbent (kWh / g) according to microwave irradiation and high-temperature calcination in the manufacturing process of metal-modified adsorbents can be used to compare manufacturing costs. In a prior study, 5 g of adsorbent, a treatment time of 1 hour, and a power consumption of 3,200 W were applied to manufacture Mg / Fe-modified biochar using high-temperature calcination (Table 3).

[0079]

[0080] In another study, 10 g of adsorbent and a treatment time of 2 hours were used to produce Ti / Mg / Zn composite modified biochar using high-temperature calcination. Since power consumption was not specified in this paper, 5,000 W was applied from the power consumption of 5,000–10,000 W suggested in a review article. In this study, which produced Mg-GAC using microwaves, 1 g of adsorbent, a treatment time of 10 minutes, and a power consumption of 3,300 W were applied. As a result, the high-temperature calcination process was found to consume 0.09–0.45 kWh / g more power per unit adsorbent and 50–110 minutes more treatment time than microwave irradiation. This suggests that using microwaves in the production of Mg-modified adsorbents is relatively more efficient than using high-temperature calcination in terms of cost and time.

[0081] conclusion

[0082] In the present invention, activated carbon was successfully modified by impregnating the surface of activated carbon with Mg and then irradiating it with microwaves. Experimental conditions, such as Mg modification conditions, pH, and reaction time, influenced the adsorption characteristics of low-concentration phosphate. The optimal modification conditions to increase phosphate removal efficiency were found to be a Mg impregnation solution concentration of 1 M, an impregnation time of 2 hours, and a microwave irradiation time of 10 minutes, while the adsorption experimental conditions were a pH of 4 and a reaction time of 180 minutes. Throughout all reaction times, the removal rate of Mg-GAC was superior to that of GAC. The reaction kinetics model was found to be suitable for a pseudo-second-order model. The adsorption process of Mg-GAC was suitable for both the Langmuir and Freundlich models. The method of modifying activated carbon using microwaves was relatively superior to existing methods in terms of processing time and power consumption. Therefore, the present invention is significant in that it presents a new method for manufacturing Mg-modified activated carbon using microwaves for the treatment of low-concentration phosphate.

Claims

Claim 1 A method for manufacturing magnesium-modified activated carbon, comprising: (1) a step of preparing activated carbon; (2) a step of impregnating the activated carbon in a 1 M Mg aqueous solution for 2 hours; and (3) a step of treating the magnesium-impregnated activated carbon in a microwave oven for 10 minutes. Claim 2 A method for manufacturing magnesium modified activated carbon according to claim 1, wherein step (3) is performed under conditions of 300~500 W, temperature 150~250℃, and maximum pressure 250~350 psi. Claim 3 A method for manufacturing magnesium modified activated carbon, wherein the activated carbon in step (1) is granular activated carbon of 0.1 to 1.0 mm. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 Magnesium-modified activated carbon produced by the manufacturing method of claim 1. Claim 8 A method for removing phosphate, comprising: a step of preparing wastewater containing phosphate; a step of adjusting the pH of the wastewater to 4; and a step of removing phosphate from the wastewater using the magnesium-modified activated carbon of claim 7. Claim 9 In claim 8, the above phosphate is H3PO4, H2PO4 in the wastewater - , HPO4 2- , PO4 3- A method for removing phosphates that exists in the form of